Evaluating software packages for attacks against elliptic curve cryptography - Moore, N (Centre for Doctoral Training in Cyber Security, 2016)
Until the coming of quantum computers and post-quantum cryptography, elliptic curve cryptography seems to be a prime candidate for modern encryption systems. Therefore producing attacks that reduce the strength of security claims about them allows researchers to better understand the practical limits of elliptic curves for cryptography {and improving their performance may potentially allow attacks to be made against the current best practice to demonstrate weaknesses. In this paper, we will be looking at how some attacks on elliptic curve cryptography work and evaluate a number of programming languages to test their suitability for implementing an attack that uses a Grobner basis calculation.